Dampak Ekonomi Pengembangan Wisata Kiram Park terhadap Pelaku Usaha di Desa Kiram - Rizali, Fikri; Rizali (PPJP ULM, 2021)
This research was conducted (1) to determine the business opportunities created after the development of the Kiram Park Tourism Object for the Kiram Village community (2) to determine the absorption of labor around the Kiram Park Tourism Object (3) to determine the income of Kiram Village business actors before and after. there is the development of Kiram Park Tourism Object. Respondents in this study amounted to 38 people, namely the community around the Kiram Park Tourism Object who are business actors. This research is a descriptive qualitative research. The data collection methods used in this study were interviews, observation and documentation. The results of this study prove that the tourism sector plays a role in the economy of the people around the Kiram Park Tourism Object, seen from the tourism sector that plays a role in the economy of the Kiram Village community, the economic impact seen from after the development of the Kiram Park Tourism Object on business opportunities, employment and increased income. The indicators used to see the economic impact are: business opportunities, employment and income after the development of the Kiram Park Tourism Object.